THE EFFECT OF USING MULTI LAYER MATERIALON DIESEL ENGINE SOUND ABSORBER CASE - Febrian, Shahrin; Buwono, Ayom; Muslim, Muswar; Arifin, Mohammad Danil; Partahi Oloan, Aldyn Clinton (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2022)
Indonesia as a maritime and archipelagic country, makes ships the only option for people to travel outside their territory to meet their daily needs. Ship routes that operate are usually from morning to evening with an average sailing time of 2-3 hours each way where these ships are generally small in size so that the engine and passengers seem to be in the same room. As a result, like it or not, the noise generated by engine noise cannot be avoided and the noise that arises will certainly greatly affect people's health if this noise exceeds a predetermined threshold value if it occurs continuously for a long time. The threshold value (NAV) of noise (caused by engine noise etc.) has been determined by local standards, namely the Regulation of the Minister of Manpower and Transmigration Number PER.13/MEN/X/2011 concerning Threshold Values for Physical and Chemical Factors in the Workplace and The Indonesian National Standard (SNI 16-7063-2004) concerning the Threshold Value of Noise and IMO Resolution of 85 decibel A (dBA). Based on the provisions above, an experiment was carried out to make Diesel engine casing from Plywood and Polyurethane and Glasswool capable of meeting the standards with an average total noise reduction of 5.5 dBA from before but an average temperature increases of 2.3 0C.